The Immune Protective Effect of the Mediterranean Diet against Chronic Low-grade Inflammatory Diseases - Casas, Rosa; Sacanella, Emilio; Estruch, Ramon (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Dietary patterns high in refined starches, sugar, and saturated and trans-fatty acids, poor in natural antioxidants and fiber from fruits, vegetables, and whole grains, and poor in omega-3 fatty acids may cause an activation of the innate immune system, most likely by excessive production of proinflammatory cytokines associated with a reduced production of anti-inflammatory cytokines. The Mediterranean Diet (MedDiet) is a nutritional model inspired by the traditional dietary pattern of some of the countries of the Mediterranean basin. This dietary pattern is characterized by the abundant consumption of olive oil, high consumption of plant foods (fruits, vegetables, pulses, cereals, nuts and seeds); frequent and moderate intake of wine (mainly with meals); moderate consumption of fish, seafood, yogurt, cheese, poultry and eggs; and low consumption of red meat, processed meat products and seeds. Several epidemiological studies have evaluated the effects of a Mediterranean pattern as protective against several diseases associated with chronic low-grade inflammation such as cancer, diabetes, obesity, atherosclerosis, metabolic syndrome and cognition disorders. The adoption of this dietary pattern could counter the effects of several inflammatory markers, decreasing, for example, the secretion of circulating and cellular biomarkers involved in the atherosclerotic process. Thus, the aim of this review was to consider the current evidence about the effectiveness of the MedDiet in these chronic inflammatory diseases due to its antioxidant and anti-inflammatory properties, which may not only act on classical risk factors but also on inflammatory biomarkers such as adhesion molecules, cytokines or molecules related to the stability of atheromatic plaque.
Keywords: Adhesion molecules